Development Strategy of Smoked Fish Product in Increasing Business Income in North Semarang District - Novita Anggrahini, Dhela; Rusdarti, Rusdarti; Muhsin, Muhsin (Journal of Economic Education, 2020)
Bandarharjo, North Semarang District has great potential to advance industrialization. The problem of this research was the decline of smoked fish product in Bandarharjo, North Semarang city. The purpose of this study was to describe the amount of costs and incomes in order to create business development strategies to overcome the obstacles faced by smoked fish entrepreneurs and increase smoked fish business income in Bandaharjo. This study used a quantitative approach. The population in this study was 25 smoked fish entrepreneurs in Bandarharjo. Data collection techniques were using interviews, documentation and questionnaires. The analysis technique used was descriptive percentage, net B / C ratio, payback period and SWOT analysis. The results of B / C ratio showed that the Period values was around 1.15, and Payback values was around 0.64. The SWOT strategy results in terms of EI strength are adequate capital, a strategic location for fumigation operations, easily accessible and can build business with relevant agencies. Then the weaknesses are business research and development has not been done, the management information system and the financial reporting system have not been running well. Opportunities offered are economic growth in Semarang significantly increased as well as the development and training of Micro Small and Medium Enterprises (MSMEs) by the government. Then the threat received is an increase in the price of raw materials.